Language-sensitive teaching as an emergent response to increasing linguistic diversity in Irish post-primary schools: Challenges, opportunities and implications for teacher education - Farrell, Angela; Masterson, Mary; Daly, Michelle (Glottodidactica, 2023)
The 21st century has been characterised by an unprecedented growth in transnational migration with education systems in many countries challenged to address the implications of this ongoing global phenomenon. This paper reports on a recent study that was undertaken amongst teachers and school managers in post-primary state schools in Ireland to explore the current position regarding language-sensitive teaching as an emergent response to the growing reality of linguistic diversity in schools. Bottom-up research of this kind is vital as it can shed light on the perceptions and experiences of the key stakeholders involved in order to determine their related professional needs and shape future directions in teacher education in this area. The key findings show that language-sensitive teaching remains in its infancy in the Irish post-primary educational context with an urgent need for teacher awareness-raising and upskilling in relation to this approach and its implementation in different subject classrooms. The research has also indicated that language support teachers can play a central role in developing language-sensitive teaching at the whole school level but this potential remains largely under-exploited in the Irish post-primary educational context.